Ecological fidelity of functional traits based on species presence-absence in a modern mammalian bone assemblage (Amboseli, Kenya). Issue 4 (2014) - Miller, Joshua H.; Behrensmeyer, Anna K.; Du, Andrew; Lyons, S. Kathleen; Patterson, David; Tóth, Anikó; Villaseñor, Amelia; Kanga, Erustus; Reed, Denné
Abstract : Comparisons between modern death assemblages and their source communities have demonstrated fidelity to species diversity across a variety of environments and taxonomic groups. However, differential species preservation and collection (including body-size bias) in both modern and fossil death assemblages may still skew the representation of other important ecological characteristics. Here, we move beyond live-dead taxonomic fidelity and focus on the recovery of functional ecology (how species interact with their ecosystem) at the community level for a diverse non-volant mammal community (87 species; Amboseli, Kenya). We use published literature to characterize species, using four functional traits and their associated categorical attributes (i) dietary mode (11 attributes; e.g., browser, grazer), (ii) preferred feeding habitat (16 attributes; e.g., grassland, woodland), (iii) preferred sheltering habitat (17 attributes; e.g., grassland, underground cavity), and (iv) activity time (7 attributes; e.g., diurnal, nocturnal, nocturnally dominated crepuscular). For each functional ecological trait we compare the death assemblage's recovered richness and abundance structure of constituent functional attributes with those of the source community, using Jaccard similarity, Spearman's rho, and the Probability of Interspecific Encounter (evenness). We use Monte Carlo simulations to evaluate whether these empirical comparisons are significantly different from expectations calculated from randomized sampling of species from the source community. Results indicate that although the Amboseli death assemblage is significantly overrepresented by large-bodied species relative to the Amboseli source community, it captures many functional dimensions of the ecosystem within expectations of a randomized collection of species. Additional resampling simulations and logistic regressions further illustrate that the size bias inherent to the Amboseli death assemblage is not a major driver of deviations between the functional ecological properties of the death assemblage and its source community. Finally, the Amboseli death assemblage also enhances our understanding of the mammal community by adding nine species and two functional attributes previously unknown from the ecosystem.